Factors influencing e-commerce channels in the life insurance industry in South Africa - Mazubane, Nokwethemba Judith (My University, 2022)
General adoption of e-commerce in South Africa is increasing in other product areas such as electronic goods, general improvement of Internet infrastructure and accessibility. Adoption of smartphone technology and cell phone penetration increases the adoption of technology and creates opportunities for the insurance market to distribute their products using these channels. Companies that master digital transformation drive significantly higher profits. With rapid change to the insurance sector driven by digital transformation, it is prudent for insurance providers to provide e-commerce channels for customers. The purpose of this study is to discover the factors that influence the success of life insurance ecommerce channels in South Africa. The basis of the study was supported by the Theory of Buyer behaviour which breaks down how a consumer goes about the process of purchasing a product. The consumer decision theory was also included to inform the basis of how consumers make purchasing decisions. To understand the adoption behaviours for technology innovations the Diffusion of innovations theory was also included in the theoretical framework. Data was collected using one on one interviews with twenty participants from a South African insurance organisation as well as customers of life insurance products. Thematic analysis was applied to the data and the findings showed that the perceptions and attitudes of consumers towards life insurance are heavily influenced by the marketing activities of the insurance provider online. The findings also showed that consumer education is a big challenge for driving adoption of e-commerce channels for this product set. The digital transformation initiatives of the organisation were also found to be a contributing factor to providing superior customer experiences to customers online. The study makes practical and empirical contribution to the insurance industry body of knowledge in South Africa.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: E-commerce; Life insurance; Technology adoption; SDG-8: Decent work and economic growth